MENINGKATKAN KEMAMPUAN MENULIS PUISI MELALUI PENDEKATAN LINGKUNGAN PADA SISWA KELAS V SDN INPRES CIKAHURIPAN - Oktaviani, Rizka Dewi Nur (2013)
Abstract : INCREASING STUDENTS' CAPABILITY IN WRITE POEM THROUGH INVOIMENT APPROACH IN INPRES CIKAHURIPAN EMELENTARY SCHOOL. The purpose of this class-action research are to improve the quality of learning process and to improve students' ability in write some poem throught pendekatan lingkungan in learning Indonesian language at Students' of Class V-A SDN Inpres Cikahuripan Bandung. The reasearch sujects were one teacher and 32 students which consisted of 14 male and 18 female. Furthermore, the instrumen was final test, sheet and teacher obsevation activities. Research finding for three cycles proved that there was improvement process toward students' learning achivement. For teachers' activities in cycles I, the average score was 2,04 categorized less, in cycle II the average score was 3,3 categorized good and in cycle III the average score was gained on 3,8 and categorized as verry good. Moreover, the improvement was also found on students' write some poem in cycle I the class average score was 61, then in cycle II the average score was 74 and ini cycle III 80 was the average score. Hence, it is concluded that invoiment approach can scientifically improve the quality of learning process and write some poem. Abstrak: MENINGKATKAN KEMAMPUAN MENULIS PUISI MELALUI PENDEKATAN LINGKUNGAN PADA SISWA KELAS V SDN INPRES CIKAHURIPAN. Penelitian tindakan kelas ini bertujuan untuk mengetahui bagaimanakah perencanaan, pelaksanaan dan hasil menulis puisi melalui penerapan pendekatan lingkungan pada siswa kelas V sekolah dasar negeri inpres cikahuripan kabupaten Bandung barat. Subjek penelitian ini adalah satu orang guru dan 32 siswa terdiri dari 14 laki-laki dan 18 perempuan. Instrumen yang digunakan adalah lembar kerja siswa, angket, dan pengamatan aktivitas guru. Dari penelitian yang dilakukan dalam 3 siklus terjadi peningkatan pada aktivitas guru dan siswa. Untuk aktivitas guru pada siklus I diperoleh nilai 2,04 dengan kategori cukup, siklus II diperoleh nilai 3,3 dengan kategori baik, siklus III diperoleh nilai 3,8 dengan kategori sangat baik. Sedangkan nilai rata-rata siswa pada siklus I adalah 61, siklus II 74 dan siklus III 80. Disimpulkan bahwa pendekatan lingkungan dapat meningkatkan kualitas proses pembelajaran dan kemampuan siswa dalam menulis puisi. Kata kunci: Menulis, Puisi, Penerapan, Lingkungan, Sekolah Dasar